Comparison of speaker dependent and speaker independent emotion recognition - Rybka, Jan; Janicki, Artur (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes a study of emotion recognition based on speech analysis. The introduction to the theory contains a review of emotion inventories used in various studies of emotion recognition as well as the speech corpora applied, methods of speech parametrization, and the most commonly employed classification algorithms.
Keywords: peech processing; emotion recognition; EMO-DB; support vector machines; artificial neural networks